Vaccination in Patients with Immunodeficiency Instructions for use of the Vaccinations recommended by the Standing Committee on Vaccination (II) Vaccination for 1. Primary Immunodeficiency Diseases and 2. HIV Infection (vol 61, pg 1034, 2018) - Ehl, Stephan; Bogdan, Christian; Niehues, Tim; Burchard, Gerd; Baumann, Ulrich; Hecht, Jane; Koch, Judith; Neubert, Jennifer; Wiese-Posselt, Miriam; Zepp, Fred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Erratum zu:Bundesgesundheitsbl (2018)10.1007/s00103-018-2761-8In der Originalpublikation dieses Beitrags fehlt ein Hinweis zu Lebendimpfungen bei Patienten mit Storungen im Bereich der Toll-like-Rezeptor-Signaltransduktion.Am Ende des letzten Absatzes unter Punk 3.6Defekte der ...
EVALuna2:36426